Prediction of strength and slump of rice husk ash incorporated high-performance concrete - Islam, Md. Nazrul; Zain, Muhammad Fauzi Mohd; Jamil, Maslina (Journal of Civil Engineering and Management, 2012)
This paper describes the development of statistical models to predict strength and slump of rice husk ash (RHA) incorporated high-performance concrete (HPC). Sixty samples of RHA incorporated HPC mixes having compressive strength range of 42–92 MPa and slump range of 170–245 mm were prepared and tested in the laboratory. These experimental data of sixty RHA incorporated HPC mixes were used to develop two models. Six variables namely water-to-binder ratio, cement content, RHA content, fine aggregate content, coarse aggregate content and superplasticizer content were selected to develop the models and ultimately to predict strength and slump of RHA incorporated HPC. The models were developed by regression analysis. Additional five HPC mixes were prepared with the same ingredients and tested under the same testing conditions to verify the ability of the proposed models to predict the responses. The results of the prediction of the models showed good agreement with the experimental data. Thus the developed models can be used to predict slump and 28-day compressive strength of RHA incorporated HPC. The research demonstrated that strength and slump of HPC could be successfully modeled using statistical analysis.